PERILAKU ADVERSITY QUOTIENT MAHASISWA DITINJAU DARI LOCUS OF CONTROL - Hartosujono Hartosujono (LP2M Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to determine whether there is a relationship between the behavior of AQ with LOC. AQ scale is the scale of a person's ability to solve problems with its capabilities. While the LOC scale is a scale that identifies the extent to which the orientation of a person's personality in the run control. Both of these variables are expected to be connecting and has a close connection. Having analyzed these two variables apparently unrelated. Of the various things that become obstacles no relationship between these variables is, because linearity is not the same, the lack of validation in the AQ scale, distance and age of the study subjects are too close.Keywords: AQ Scale, Scale LOC, personality, and solve problems